Food‐Derived Xeno‐microRNAs: Influence of Diet and Detectability in Gastrointestinal Tract—Proof‐of‐Principle Study - Link, Jastin; Thon, Cosima; Schanze, Denny; Steponaitiene, Ruta; Kupcinskas, Juozas; Zenker, Martin; Canbay, Ali; Malfertheiner, Peter; Link, Alexander (Molecular nutrition & food research, 2019)
Scope Diet is amongst the most crucial factors contributing to the multistep process of carcinogenesis. The role of exogenous microRNAs (miRNAs) is still debatable. In this proof‐of‐principle work, the presence of miRNAs in a variety of foods, its stability to processing, and detectability in GI mucosa and feces are studied and the effect of short‐term diet on human‐ or plant‐derived miRNAs in feces and blood is examined. Methods and results Animal and plant miRNAs are detected in all foods irrespective of processing. Animal‐derived foods showed the highest miRNA level and the lowest is found in cheese and milk. The impact of the short‐term vegetarian or meat‐rich diet on blood and feces miRNA is evaluated in healthy subjects using qPCR and Affymetrix profiling. Diet is not associated with changes in ultraconserved miRNAs. However, a vegetarian diet is associated with an increase of miR‐168 in feces but not in blood. Overall, plant miR‐168 is detectable in normal GI mucosa and in colorectal cancer. Conclusions Food provides a great source of miRNAs and diet may be associated with changes in xenomiRs. Plant‐derived miR‐168 is ubiquitously present in feces, normal mucosa, and cancer. Further studies are needed to evaluate the functional interaction between diet‐derived miRNAs and GI tract. Exogenous microRNAs are suggested to trigger gastrointestinal diseases. Here, it is shown that food may provide a great source of microRNAs. The diet challenge described in this study is associated with an increase in plant microRNA miR‐168 in feces while no changes in ultraconserved microRNAs are observed. Detectability of miR‐168 in gastric and colon mucosa, colorectal cancer, and peritoneal fluid suggests its functional role.